E-business Technology and Strategy International Conference, CETS 2010, Ottawa, Canada, September 29-30, 2010. Proceedings - Zaman, Marzia; Liang, Yawei; Siddiqui, Sohail M.; Wang, Tim.; Liu, Vincent; Lu, Ceecee; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the proceedings of the International Conference on E-business Technology and Strategy held in Ottowa, Canada, in September 2010.
Research on Group Decision-Making Mechanism of Internet Emergency Management -- The Challenges and Issues Regarding E-Health and Health Information Technology Trends in the Healthcare Sector -- The Study of Address Tree Coding Based on the Maximum Matching Algorithm in Courier Business -- Customer Credit Scoring Method Based on the SVDD Classification Model with Imbalanced Dataset -- K-BRiR: An Efficient and Self-organized Routing Mechanism for Structured Peer-to-Peer Service Networks -- Study on Amortization Time and Rationality in Real Estate Investment -- Risk Evaluation of Business Continuity Management by Using Green Technology -- Automated Methodologies for the Design of Flow Diagrams for Development and Maintenance Activities -- ACO-Based Projection Pursuit: A Novel Clustering Algorithm -- Ant Colony Algorithm for Multiple-Depot Vehicle Routing Problem with Shortest Finish Time -- Chaos Caused by a Transitive Map in Information -- Comparative Study of Methods for Monitoring and Controlling a Regional Economic System -- Energy Levels and Co-evolution of Product Innovation in Supply Chain Clusters -- A Typology Framework of Loyalty Reward Programs -- The Knowledge Transfer Factors under Different Perspectives -- IT Operational Risk Measurement Model Based on Internal Loss Data of Banks -- Prediction Task Assignment of Multi-UAV Approach Based on Consensus -- A Macroscopic Timing Optimization Model for Signalized Intersections Based on an Extended Internal State Node Model -- A Research Methodology for Green IT Systems Based on WSR and Design Science: The Case of a Chinese Company -- Research on the Hotel Image Based on the Detail Service -- Impact of Network Information on the Management of Library E-Resources -- Technology Route and System Design of Green IT -- The Tail of BPM -- The Aggregation-Diffusion Model of Conduction of Technology Value in the Large-Scale Sports Events -- Specification Patent Management for Web Application Platform Ecosystem -- Evaluation of the Acceptance of Audience Response System by Corporations Using the Technology Acceptance Model -- Identification of Variables and Factors Impacting Consumer Behavior in On-line Shopping in India: An Empirical Study -- Knowledge Model of Emergency Decision-Making Based on Knowledge Supply and Demand -- The Consistency and Ranking Method Based on Comparison Linguistic Variable.
Keywords: Computer science; Database management; Information storage and retrieval systems; Information systems; Information Systems; Computer Science; Management of Computing and Information Systems; e-Commerce/e-business.; Information Systems Applications (incl.Internet).; Computers and Society; Information Storage and Retrieval; Database Management